Double outlet right ventricle with L-position of the aorta, D-loop, subaortic VSD, and pulmonary stenosis. Issue 5 (October 1976) - Caffarena, J M; Sanchez, F G; Concha, M; Gomez-Ullate, J M; Peris, J J; Frias, R; Otero, E; Ferrer, H; Montero, A
Abstract : We describe a case of double outlet right ventricle with subaortic ventricular septal defect and pulmonary stenosis treated successfully with cardiopulmonary bypass. We consider the clinical history and angiocardiographic and surgical findings of this rare anomaly. We stress the difficulties of reconstruction of the outflow tract of the right ventricle, because of the anomalous pathway of the right coronary artery, the posterior situation of the pulmonary artery, and the abnormal anatomy present in the outflow tract of the right ventricle.